(untitled) (Olhares, 2015)
Interview with Ednaldo Freire. Ednaldo Freire, partner of Luís Alberto since the foundation of the Fraternal Companhia de Arte e Malas-Artes in 1993, he had elected the universe of popular commedy as a work field. More than three decades dedicated to theatrical activity in Brazil, recognized by his achievement, he is interviewed in this edition from Olhares. Admiror of circus and mambembe theater, he is concerned with the genre Comic and humor in popular comedy, his trajectory reflects a search popular theater that is, at the same time, stimulating to think the social relations. Heir of Brecht and his political theater, Ednaldo talks about the need of a “ready actor”, awake by an education that do not discard the genre Comic from the base on its acting.